Gut Microbiota Play an Essential Role in the Antidiabetic Effects of Rhein. (9th July 2018) - Wang, Ruifeng; Zang, Pu; Chen, Junxiu; Wu, Fei; Zheng, Zhouqin; Ma, Jian; Yang, Cuihua; Du, Hong
Abstract : It is clear that the gut microbiota can affect host metabolism and alterations of the gut microbiota can link with metabolic disease. Rhein has been used in traditional Chinese medicine with putative antidiabetic effects. Here we show that oral administration of rhein for 6 weeks can significantly reduce fasting blood glucose (FBG) level (8.30 ± 4.52 mmol/l versus 18.89 ± 6.06 mmol/l, p < 0.01), elevate the active glucagon-like peptide 1 (GLP-1) level (22.21 ± 2.61 pmol/l verss 14.46 ± 5.22 pmol/l, p < 0.05), and increase the number of L-cells in the terminal ileum. The antidiabetic effect of rhein is abrogated in db/db mice treated with rhein in combination with broad-spectrum antibiotics. We observed that the abundance of the Bacteroidetes is increased in mice treated with rhein (0.361±0.022 versus 0.185 ± 0.055, p < 0.05, ). In addition, there is no significant difference in diversity between rhein-treated groups and the controls (Shannon index: p = 0.88; Simpson index: p = 0.86). Taken together, our results indicate that modulation of the gut microbiota may play an essential role in the antidiabetic effects of rhein.